al ‘Ala>qah Baina Kafa>ah al Mufrada>t wa Maha>rah al Insya’ al Muwajjah Li Tullab as S}off al ‘Aq Bogem Jombang - Fira Kumala Devi; Isniyatun Niswah; Siti Durrotun Naseha (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2024)
The purpose of teaching Arabic it is not to describe students' ability to master the four skills, namely listening, speaking, reading and writing. Besides that, there are also elements of language education such as sounds, grammar, and vocabulary that help in achieving educational goals. Writing skill is one of the skills in teaching Arabic. Vocabulary meaning is a collection of words or vocabulary that is known by a person, other entity, or part of a particular language. Vocabulary competence in teaching Arabic is very important. For this reason, students need to improve vocabulary mastery to master four Arabic skills, namely reading skills, writing skills, listening skills, and speaking skills. The formulation of the problem in this study is: How is the efficiency of vocabulary in learning Arabic in class X MTs At-Taufiq Bogem Jombang? How are writing skills to create orientation in learning Arabic for class X students at MTs At-Taufiq Bogem Jombang? And what is the relationship between vocabulary efficiency and writing skills? This research method is a quantitatif research to determine the relationship between vocabulary competence and directed construction skills. Analyzing the data using the independent variable denoted by the letter (X) is vocabulary efficiency. The dependent variable which is denoted by the letter (Y) is directed construction skills. The sample of this research is the students of class X MTs At-Taufiq Bogem Jombang. Evidence was collected using 13 and 12 question tests. Hypothesis testing uses statistical tests to test the product moment correlation. The results showed that there was a relationship between vocabulary competence and directed construction skills.